Analisis Keterlambatan Pengembalian Buku di Perpustakaan Pusat Grha Kandaga Universitas Padjadjaran - Rumaisha Nur Farriza; Nadia Nila Farodisa; Prijana Prijana; Evi Nursanti Rukmana (Universitas Sebelas Maret Library, 2024)
Rules are made to ensure everything goes as planned. But people sometimes break the rules. The Unpad Central Library has a problem with users returning books late. This study aims to understand how library users feel about late returns. This study uses a quantitative approach to test a theory and prove a hypothesis. Variable X is the users' attitude, while variable Y is the action of returning books late. A quota sampling method was used to select 100 samples from a population of 189 library users who borrowed collections in June 2024 and returned them late. The test results show that there is a moderate correlation between library users' attitudes and the act of returning collections late. Users of Grha Kandaga Unpad Central Library know the rules about returning books. This affects how they feel and judge situations where users are late. This makes them make decisions based on their attitudes. Through this research, the library can understand how users respond to late returns. This helps the library improve its strategies to prevent unauthorized borrowing, especially related to the late return of book collection.